1977
DOI: 10.1080/00223980.1977.9915859
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Self and Ideal Self Ratings in Relation to High and Low Levels of Anxiety in College Women

Abstract: The Cattell and Scheier IPAT Anxiety (Self Analysis) Questionnaire and the Corsini SAQS Chicago Q Sort were administered to 146 college women. Ss were divided into "high" and "low" anxiety groups on the basis of the IPAT anxiety scores. Those women with a high degree of anxiety were found to have a significantly greater discrepancy between their perceived self and ideal self concepts than did those women who had low levels of anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…They found that women with higher anxiety displayed greater discrepancy between their perceived selves and their ideal selves. The results of this study were published in the Journal of Psychology (Shand and Grau ). This research had served as Grau's honors thesis at Gettysburg College; with Shand's help they published the manuscript together.…”
Section: John “Jack” Shand: a Lifementioning
confidence: 99%
“…They found that women with higher anxiety displayed greater discrepancy between their perceived selves and their ideal selves. The results of this study were published in the Journal of Psychology (Shand and Grau ). This research had served as Grau's honors thesis at Gettysburg College; with Shand's help they published the manuscript together.…”
Section: John “Jack” Shand: a Lifementioning
confidence: 99%
“…Where the two remain widely divergent, that is, where the individual's assessment of himself as he currently is differs markedly from the ideal state he would like to attain, he/she tends to be vulnerable to dysphoric emotions such as disappointment, dissatisfaction, depression and frustration (Abelson, 1983;Carver and Ganellen, 1983;Kemper, 1978;Roseman, 1984). Wide discrepancy between the real self and the ideal self has also been found to be associated with insecurity (Puham, 1976), anxiety (Shand and Graw, 1977), neuroticism and the need for psychological counselling (McClure et af., 1982).…”
mentioning
confidence: 96%